MODERN INSTALLATION PROCESS OF PRE-ENGINEERED STEEL BUILDING - MD. SUMON REZA,; SHAMMYA AFROZE,; ABUL K. AZAD, (International Journal of Innovations in Engineering Research and Technology, 2021)
In our construction sector Pre-engineered building (PEB) system is the new concept. It has huge advantages including economical solution, easier fabrication and prompt Installation which reduced time and cost. The present work represents the Installation process of steel building which involves with the gathering of steel materials into a structure on the site. This process briefly describes the materials unloading, lifting, placingthe materials into better position and then assembles them as an entire member by bolting. The processes must be completed with quickly, safely and economically. Installation cost varies around 10-12% of the whole project price which is primarily dependent on the speed of installation of the building. If we do the Installation carefully the cost will be minimized with maintaining safety. By this we can assure the safe Installation procedures and structural stability of the building. To focus all these relevant aspects the procedure for the Installation process are describe in this paper.